ANALISIS KUALITATIF PEWARNA KUNING PADA KUNYIT BUBUK YANG BEREDAR DI BANDA ACEH - Adriani Azmalina (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
Yellow Dyes On Turned Turns is a spice that is often used by the people of Aceh, to get a good color of turmeric, producers usually add food coloring to the use of which must be in accordance with the rules. The purpose of this study was to identify the use of yellow dyes which are prohibited in powdered turmeric circulating in Banda Aceh. The research method was carried out descriptively in the Pharmacy and Food Analyst laboratory using thin layer chromatography (TLC). With 12 samples of powdered turmeric circulating in Banda Aceh, the results obtained from the study of four non-positive samples containing curcumin (natural yellow coloring), five unbranded samples and three branded samples containing tartrazine (synthetic yellow dye permitted).Keywords: Turmeric powder; Thin layer chromatography